2019
DOI: 10.1111/dme.14166
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vestibular stimulation on metabolism and body composition

Abstract: Obesity, diabetes and metabolic disease represent an ongoing and rapidly worsening public health issue in both the developed, and much of the developing world. Although there are many factors that influence fat storage, it has been clearly demonstrated that the homeostatic cornerstone of metabolism lies within the hypothalamus. Moreover, neuronal damage to vital areas of the hypothalamus can drive reregulation or dysregulation of endocrine function, energy expenditure and appetite, thereby promoting a shift in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
2
19
0
1
Order By: Relevance
“…Alternatively, a review by Sailesh et al proposed that vestibular stimulation affects diabetic state by increasing insulin secretion through modulating autonomic nerve activity based on some preliminary evidence [33]. Moreover, the vestibular system might affect glucose and energy metabolism through various endocrine factors, including cortisol and thyroid hormone [21]. Since VL significantly suppressed serum insulin levels elevated by HSHFD and the slight, but not calorie intake from control (Cont) and aVL mice fed ND or HSHFD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, a review by Sailesh et al proposed that vestibular stimulation affects diabetic state by increasing insulin secretion through modulating autonomic nerve activity based on some preliminary evidence [33]. Moreover, the vestibular system might affect glucose and energy metabolism through various endocrine factors, including cortisol and thyroid hormone [21]. Since VL significantly suppressed serum insulin levels elevated by HSHFD and the slight, but not calorie intake from control (Cont) and aVL mice fed ND or HSHFD.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term space flight increases insulin resistance and impairs the vestibular function in astronauts [3,20]. Several centrifugation studies suggest that the macular gravity receptor (MGR) influences the Medial Vestibular Nucleus (MVe) and further projects into many of the homeostatic nuclei of the brain stem and hypothalamus that are responsible for energy regulation and metabolic homeostasis [21]. Fuller et al reported that wild-type mice subjected to vestibular stimulation via centrifugation for a period of 8 weeks exhibit an initial decrease in food intake and prolonged body fat reduction, which are not observed in macular otoconia-deficient mice [22].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the vestibular system can be stimulated by way of electrical current delivered via self-adhesive pads on the mastoid processes, frequently known as Galvanic Nerve Stimulation [19][20][21][22][23][24] or Vestibular Nerve Stimulation (VeNS) [25]. Early clinical research has reported that VeNS improves postural stability in persons with Parkinson's Disease [19][20][21], bilateral vestibulopathy [22], and the elderly population [23][24], potentially via vestibular neuroplasticity and enhanced vestibular information processing [23], however there is a paucity of evidence in people with CP.…”
Section: Introductionmentioning
confidence: 99%